PENETAPAN KADAR FENILBUTAZON DAN PARASETAMOL DIDALAM JAMU PEGAL LINU YANG BEREDAR DI KOTA MALANG SECARA KROMATOGRAFI LAPIS TIPIS DENSITOMETRI - Rollando Rollando; Erizcha Debora Embang; Eva Monica (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2019)
Traditional medicine or commonly known as herbal medicine is often found, because its free to use without consulting medical therefore. Chemical drugs in the herbal products are still often found. Drug chemicals often added to herbs are paracetamol and phenylbutazone. In this study TLC Densitometry system used to detect paracetamol and phenylbutazone, to get optimal TLC system, validation includes selectivity, linearity, accuracy, precision, LOD and LOQ, determination of paracetamol and phenylbutazone in herbal samples.Optimal mobile phase for detection paracetamol and phenylbutazone is ethyl acetate : chloroform (2:1). Maximum wavelength of 240 nm paracetamol, 237 nm phenylbutazone. The method used has selectivity, linearity and met the criteria of accuracy and precision, but the limit detection and limit quantitation do not met requirements. The result of the study 30 samples of herbs, found 5 samples were positive containing phenylbutazone that samples j, k, s, u and v with successive percentpercentages of 9,5053%; 10,6138%; 62,8776%; 42,8839% and 24,9238%.